The Influence of Organizational Justice and Organizational Culture on Employee Loyalty - Ding Chong (Dinasti International Journal of Management Science, 2022)
The literature review article on the Effect of Organizational Justice and Organizational Culture on Employee Loyalty is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Organizational Justice affects Employee Loyalty; and 2) Organizational Culture has an effect on Employee Loyalty. Apart from these 2 exogenous variables that affect the endogenous variable Employee Loyalty, there are still many other factors including Wages, Workload, Work Environment and Leadership variables.